NASA Robotic Mining Competition - Buchmann, Tim J (Proceedings of the Wisconsin Space Conference, 2019)
The sky’s the limit, so the saying goes, yet humankind is trying to make a footprint on our neighbor Mars. Because of Mars distance from Earth, NASA would like to develop a mechanism to help astronauts to collect water crystals found below the sandy Martian regolith. As a result, they task the Robotic Mining Competition (RMC) teams to design a robot that can steer through a simulated Martian terrain, collect gravel (simulated water crystals) located under the regolith material (BP-1), and bring the gravel back to the collection bin. The RMC teams must work cooperatively in order to design and build such a robot, and to out-compete all their competitors. New solutions are being developed from colleges and universities all over the country to discover new mechanisms that can collect water crystals through a mining robot. These students have taken their skills from their schools, their internships, and clubs to apply their theory and design to develop these new mechanisms. From this program, these students created outreach programs to encourage science, technology, engineering, and mathematics to local communities by volunteering through mentorship programs and after-school activities.